Karakteristik Populasi Rayap Tanah Coptotermes spp (Blattodea: Rhinotermitidae) dan Dampak Serangannya - Subekti, Niken (Biosaintifika: Journal of Biology & Biology Education, 2010)
Termite are known to infest building in the tropics, but in their quest for cellulose they may also cause signifi cant damage to crops and trees. They become pest only when their natural habitat is altered in some way by humans. Subterranean termite Coptotermes spp has been known as the most economically important structural pest in Indonesia. Due tomorphological ambiguity, traditional identifi cation of Coptotermes spp. has always been diffi cult and unreliable. In economic point of view, economic loss due to termite attack always increases every year, and in the year 2000 it is estimated to reach 373 million US$. Moreover, the social as well as ecological impact caused by termite attack should also be considered. In the capital city of Jakarta, the subterranean termite attack on home buildings reaches around 55%; while in Surabaya (East Java) 36%; and in Semarang (Central Java) 41%. Meanwhile, in some other cities, the subterranean termite attack on home buildings reaches on the average of 20%. The presence of termites in a region can depend on various factors, such as soil and vegetation type. Climatic features andwater avaibility play an important part in termite survival. Daily and seasonal changes in these factors also affect termite distribution.Keywords: characteristics, climatic, Coptotermes spp, attack impact.